CLINICAL PHARMACOLOGICAL APPROACH TO THE SELECTION AND USE OF DRUGS USED IN GASTROINTESTINAL DISEASES (World Bulletin of Public Health, 2024)
Currently, in gastroenterology, much attention is paid to disorders of the motor function of the digestive tract. This is due to the fact that, as studies of recent years have shown, disorders of the gastrointestinal tract motility can act as a leading pathogenetic factor contributing to the development of many common gastroenterological diseases, such as functional dyspepsia, gastroesophageal reflux disease (GERD), duodenogastric reflux. All of them significantly worsen the quality of life of patients, limiting their work and social activities, and at the same time can cause serious complications, such as Barrett's esophagus, esophageal adenocarcinoma, stomach cancer and others.